Paternal developmental thyrotoxicosis disrupts neonatal leptin leading to increased adiposity and altered physiology of the melanocortin system - Martinez, Maria Elena; Wu, Zhaofei; Hernandez, Arturo (Frontiers in Endocrinology, 2023)
Background The genetic code does not fully explain individual variability and inheritance of susceptibility to endocrine conditions, suggesting the contribution of epigenetic factors acting across generations. Methods We used a mouse model of developmental thyrotoxicosis (Dio3-/- mouse) to analyze endocrine outcomes in the adult offspring of Dio3-/- males using standard methods for body composition, and baseline and fasting hormonal and gene expression determinations in serum and tissues of relevance to the control of energy balance. Results Compared to controls, adult females with an exposed father (EF females) exhibited higher body weight and fat mass, but not lean mass, a phenotype that was much milder in EF males. After fasting, both EF females and males exhibited a more pronounced decrease in body weight than controls. EF females also showed markedly elevated serum leptin, increased white adipose tissue mRNA expression of leptin and mesoderm-specific transcript but decreased expression of type 2 deiodinase. EF females exhibited decreased serum ghrelin, which showed more pronounced post-fasting changes in EF females than in control females. EF female hypothalami also revealed significant decreases in the expression of pro-opiomelanocortin, agouti-related peptide, neuropeptide Y and melanocortin receptor 4. These markers also showed larger changes in response to fasting in EF females than in control females. Adult EF females showed no abnormalities in serum thyroid hormones, but pituitary expression of thyrotropin-releasing hormone receptor 1 and thyroid gland expression of thyroid-stimulating hormone receptor, thyroid peroxidase and iodotyrosine deiodinase were increased at baseline and showed differential regulation after fasting, with no increase in Trhr1 expression and more pronounced reductions in Tshr, Tpo and Iyd. In EF males, these abnormalities were generally milder. In addition, postnatal day 14 (P14) serum leptin was markedly reduced in EF pups. Discussion A paternal excess of thyroid hormone during development modifies the endocrine programming and energy balance in the offspring in a sexually dimorphic manner, with baseline and dynamic range alterations in the leptin-melanocortin system and thyroid gland, and consequences for adiposity phenotypes. We conclude that thyroid hormone overexposure may have important implications for the non-genetic, inherited etiology of endocrine and metabolic pathologies.